Absolute seat movement - Kleshnev, V. (BioRow, 2024)
Did you know that absolute seat movements are more than two times smaller in magnitude than the boat movements? This implies that higher inertial rowing efficiency should be associated with a decrease in the variation of absolute seat velocity (and the rower`s mass), rather than the boat velocity.